2017
DOI: 10.1136/sextrans-2016-052948
|View full text |Cite
|
Sign up to set email alerts
|

How to do it: setting up an asymptomatic screening pathway for men who have sex with men

Abstract: Many STIs are known to disproportionately affect men who have sex with men (MSM) in the UK; therefore, regular asymptomatic screening that is easy to access is vital among this group. Asymptomatic screening pathways can reduce long clinic waits, which may encourage more people to attend for screening. We therefore developed and trialled an asymptomatic pathway for MSM within our service. This extended our previous pathway, which allowed asymptomatic service users to fill in a questionnaire and see a healthcare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…15 On the contrary, asymptomatic STIs were common in women and MSM, 15 hence warranting the need for more frequent screening in these populations. 16 In 2002, the United Kingdom implemented a chlamydia screening program for women and men under the age of 25 in clinical and nonclinical settings. 17…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 On the contrary, asymptomatic STIs were common in women and MSM, 15 hence warranting the need for more frequent screening in these populations. 16 In 2002, the United Kingdom implemented a chlamydia screening program for women and men under the age of 25 in clinical and nonclinical settings. 17…”
Section: Discussionmentioning
confidence: 99%
“…15 On the contrary, asymptomatic STIs were common in women and MSM, 15 hence warranting the need for more frequent screening in these populations. 16 In 2002, the United Kingdom implemented a chlamydia screening program for women and men under the age of 25 in clinical and nonclinical settings. 17 Multivariate analysis using logistic regression showed that that STIs were significantly more likely to be diagnosed in patients who attended the north clinic compared to those who attended the south clinic (OR: 6.65; 95% CI: 3.86-11.46).…”
Section: Discussionmentioning
confidence: 99%
“…While we continue to publish case reports and case series, these draw on new technologies—a case in point is Davey’s study of syphilitic aortitis 3. We regularly publish educational articles addressing structural issues such as new screening pathways which go beyond the care of specific conditions 4. Access to and provision of services beyond the badged STI clinic setting has been a growing theme for many years 5.…”
mentioning
confidence: 99%